Prognostic significance of stress hyperglycemia ratio in acute coronary syndrome patients with prior coronary artery bypass grafting - Ma, Xiaoteng; Chu, Huijun; Li, Qiuxuan; Yang, Yuxiu; Zhou, Yujie; Wang, Zhijian (Frontiers in Endocrinology, 2026)
BackgroundPatients with prior coronary artery bypass grafting (CABG) presenting with an acute coronary syndrome (ACS) constitute a subgroup at high cardiovascular risk and have a poor prognosis even after percutaneous coronary intervention (PCI). The stress hyperglycemia ratio (SHR) is a novel marker reflecting acute hyperglycemia adjusted for chronic glycemic status, but its prognostic value in this specific population remains unknown. This study aimed to investigate the association of SHR with long-term adverse cardiovascular outcomes in ACS patients with prior CABG.MethodsThe SHR was calculated using the following formula: admission fasting blood glucose (AFBG)/[1.59 × glycosylated hemoglobin A1c (HbA1c) - 2.59]. The primary endpoint was the long-term incidence of major adverse cardiovascular and cerebrovascular events (MACCE), a composite of all-cause death, non-fatal stroke, non-fatal myocardial infarction, or unplanned revascularization.ResultsA total of 1,208 ACS patients with prior CABG who underwent PCI were included in the final analysis. During a median follow-up of 1,291 days, 368 (30.5%) patients developed at least one primary endpoint event. Kaplan-Meier analysis revealed a graded, positive relationship between the SHR tertiles and the follow-up incidence of MACCE (log-rank P < 0.001). In multivariate Cox proportional hazards regression analysis adjusted for GRACE risk score and other confounders, compared with those in the lowest SHR tertile, patients in the middle and highest tertiles had a higher risk of MACCE (adjusted hazard ratio [HR]: 1.557, 95% confidence interval [CI] 1.166-2.079, P = 0.003, and 1.943, 95% CI 1.476-2.557, P < 0.001, respectively). Similar results were obtained when SHR was analyzed as a continuous variable (adjusted HR per unit increase 1.276, 95% CI 1.105-1.474, P = 0.001). The addition of SHR to the baseline reference prediction model including GRACE risk score improved model predictive performance markedly (C-statistic: increased from 0.559 to 0.626, P = 0.002; cNRI: 0.580, P = 0.016; IDI: 0.133, P = 0.010).ConclusionsIn ACS patients with prior CABG undergoing PCI, an elevated SHR was a strong and independent predictor of long-term MACCE. This simple metric provides potent prognostic information, potentially enhancing risk stratification and guiding management in this high-risk patient population.